Adapting the Wheelchair Skills Program for pediatric rehabilitation: recommendations from key stakeholders - Geneviève Daoust; Paula W. Rushton; Marissa Racine; Karolann Leduc; Najoua Assila; Louise Demers (BMC, 2021)
Abstract Background Backed by over 20 years of research development, the Wheelchair Skills Program (WSP) has proven to be a safe and effective program to improving wheelchair skills for adult wheelchair users. However, evidence is lacking for the pediatric population, which may help to explain the limited use of the WSP in pediatric settings. While additional evidence specific to the pediatric population is needed, concurrent implementation of the WSP into pediatric clinical practice is equally prudent to allow those users to benefit from the years of accumulated WSP evidence. To facilitate implementation of evidence-based programs into practice, adaptation is also often required to improve the fit between the program and the local context. Therefore, the objective of this study was to understand what adaptations, if any, are required for the WSP to be implementable in a pediatric setting. Methods A deductive qualitative descriptive study design was used, guided by the Knowledge to Action Framework and Consolidated Framework for Implementation Research (CFIR). Occupational Therapists (OTs) from a pediatric rehabilitation center and two specialized schools in Montreal, Canada were invited to participate in a 90-min focus group. The Framework Method was followed for the data analysis. Results One focus group in each site (n = 3) was conducted with a total of 19 participants. From the OTs' perspectives, our analysis revealed benefits of WSP use and various issues (e.g. some skills seem unrealistic) affecting its uptake in relation to the constructs of the CFIR Intervention Characteristics domain. The results provided guidance for the recommendations of adaptations (e.g. addition of a caregiver assistance score) to enhance implementation of the WSP in pediatric rehabilitation settings and helped to identify the need for the production of new knowledge and knowledge translation (KT) tools. Conclusions Implementation of the WSP with the adaptations and KT tools proposed could allow pediatric manual wheelchair users to improve their wheelchair skills.